Pasar Digital dan Eksploitasi Data: Mengatasi Penyalahgunaan Dominasi Berdasarkan Hukum Persaingan Usaha Indonesia - Taufiqurrohman, Moch. Marsa; Lita, Helza Nova; Adrian Pah, Gress Gustia (Jurnal Penelitian Hukum De Jure, 2025)
Practices exploiting personal data, particularly by dominant players, can lead to unfair competitive advantages. The power derived from service providers' access and control over users' data can capture the market from existing competitors and potential entrants, potentially resulting in higher and even discriminatory consumer prices. This article, employing a combination of normative juridical research and Reform-Oriented Research methodology, aims to establish the exploitation of personal data as a form of abuse of the dominant position in the digital market under Indonesian competition law. The article argues that the practices of digital service providers exploiting personal data, facilitated by the conditions of the digital market and their dominant positions, create barriers for competitors and deter potential entrants. This ultimately meets the element of abuse of dominant position under Article 25 of Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition, rendering such practices per se illegal. The article concludes by suggesting that lawmakers should establish a framework and adequate regulations to address the exploitation of personal data by business actors in the digital market. This would promote fair business competition and protect the interests of digital service users.